Bifurcating Worlds? A Systematic Review of How Visual and Language Data Are Combined to Study Teachers and Their Teaching. Issue 1 (March 2020) - Schachter, Rachel E.; Freeman, Donald; Parakkal, Naivedya
Connecting teachers' perspectives with their practice is an enduring challenge shaping what and how we understand teaching. Researchers tend to bifurcate teachers' work between their private and their public lives. These "worlds" bring particular meanings that are rendered through the analyses of visual documentations of teaching and teachers' language-based accounts of their teaching. Combining these two forms of data is a basic research challenge both operationally and conceptually. Operationally, the researcher determines how the forms are connected and which decisions reflect (and are anchored in) conceptual warrants. This review identified 52 studies that combine visual and language data to study teachers and teaching to examine how data were collected and analyzed in the studies and what types of the theoretical frameworks were used to warrant the interpretations resulting from the connections. The review found only seven studies that balanced both worlds by explicitly warranting how the two forms of data were interconnected. Otherwise, most studies foregrounded one form of data and drew on the other to support or explain the first. Whereas most of the authors rationalized the connection between the forms of data in their studies, few took the more complex step of theorizing how the two worlds were connected. We argue that such incomplete connections risk inaccurately representing the work of teaching. We propose some design questions and research procedures that researchers may use to avoid bifurcating teachers' worlds.